Evaluation of osteogenic design factors in electrospun poly(ε-caprolactone) nanofiber scaffolds - Ruckh, Timothy T., author; Popat, Ketul, advisor; James, Susan, committee member; Kipper, Matt, committee member; Ryan, Stewart, committee member (Colorado State University. Libraries, 2010)
Biodegradable bone tissue scaffolds have the potential to impact patients with numerous ailments. Starting with fabrication techniques that produce nano-scale features, the ability to manipulate architecture, alter surface chemistry, and deliver biological molecules allows for the design of elegant and highly effective bone scaffolds. This work aimed to develop a porous, nanofiber scaffold with osteogenic design features the capability to deliver an antibiotic molecule from within the nanofibers. Two osteogenic design factors with unique mechanisms of action were selected; hydroxyapatite nanoparticles and oleic acid. Hydroxyapatite (HAp) is the primary inorganic phase of natural bone tissue and has been used to more closely mimic the extracellular environment of synthetic bone tissue scaffolds. Oleic acid (OLA) is an ω-9 fatty acid with suspected osteogenic effects due to activation of peroxisome proliferator-activator receptors (PPARs). In separate in vitro evaluations, OLA significantly increased osteoblast phenotypic behaviors and led to differential expression of the three PPAR isoforms, suggesting that the OLA is activating its anticipated receptor. HAp produced mixed results by inducing a small increase in alkaline phosphatase activity, but decreasing expression levels of bone matrix proteins. An in vivo evaluation of biocompatibility revealed that neither design factor increased the inflammatory response over control nanofiber scaffolds in paravertebral muscle pouches. However, both factors separately increased new osteoid production. Scaffolds with both HAp and OLA elicited the greatest osteogenic response in vivo, suggesting positive synergy between the two design factors. Finally, rifampicin (RIF), an antibiotic molecule was loaded into the nanofibers, and its release into static bacterial culture was effective in inhibiting bacterial population growth for both a Gram-positive and Gram-negative bacterial strain, separately. Overall, these nanofiber scaffolds were demonstrated to be effective carriers of soluble (OLA, RIF) and insoluble signals (HAp) which can modulate cell behaviors. Future work will aim to incorporate additional osteogenic features into the scaffolds and to develop multiple antibiotic release mechanisms from the nanofibers.
Keywords: osteoblast; nanofiber; scaffold; bone; delivery